Use of 'Open Data' in Urdu Literature Research and its Effectiveness - Mohsin (IDEA PUBLISHERS, 2020)
'Open Data' is gaining momentum in literature and language for research. 'Open Data' is a collection of easily accessible data that is to be available for general use without any restrictions. The Open Data analysis has been taken up in contemporary period by almost every government in the world. This paper describes how some of the Urdu researchers' tasks could be conducted, bringing a new actor in the ecosystem. The paper investigates are the objectives of opening the data in Urdu Literature, and how can researchers get the maximum benefit? Both qualitative and quantitative data collection methods are used. Interviews and survey research strategies are employed and data collected from four user groups, including popular websites like Rekhta, Urdu media, and Urdu research journals. The study implied the deductive method, which incorporated a top-down approach. There are plenty of data sources that might provide a different perspective and large public datasets from various authors, countries, and literary agencies. The results show the positive impact of 'Open Data' with context to the Urdu Literature.